PEMANFAATAN WHATSAPP SEBAGAI MEDIA PEMBELAJARAN IPS DI MASA PANDEMI COVID 19 PADA PESERTA DIDIK KELAS VIII B SMP NEGERI 11 PONTIANAK - Saripah Aini; Sulistyarini Sulistyarini; Sri Buwono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the use of Whatsapp media in the socialstudies learning process during the Covid 19 pandemic and theobstacles in using WhatsApp in class VIII students. B SMP Negeri 11Pontianak. This study uses a qualitative approach in the form ofdescriptive research. Data collection techniques used in this studywere direct observation, interviews and documentation studytechniques.students B SMP Negeri 112) Barriers to the Use ofWhatsapp Social Media for Class VIII Students B, namely whatsappsuch as group video calls have limitations in the number of uses andusage must be connected to internet services to use the whatsappapplication if not connected will hamper the online learning process